MEDICAL IMAGING AND 3D RECONSTRUCTION FOR OBTAINING THE GEOMETRICAL AND PHYSICAL MODEL OF A CONGENITAL BILATERAL RADIO-ULNAR SYNOSTOSIS - KARPIŃSKI, Robert; JONAK, Józef; MAKSYMIUK, Jacek (Applied Computer Science, 2018)
The paper presents results of a 3D reconstruction of a congenital bilateral radio-ulnar synostosis. Basics of anatomy and biomechanical analysis of the elbow joint were introduced. Case report of a congenital bilateral radio-ulnar synostosis was presented. Based on the data from computed tomography imaging, the model of a congenital bilateral radio-ulnar synostosis was constructed. Basic information on reverse engineering, rapid prototyping and methods of making physical models are presented. The creation of physical models was aimed at pre-operative planning and conceptualization. Physical models were also used in the educational form at the stage of communication with the patient.